The reliability of pre-participatory screening tests used on sports participants - Zumana, Nosipho Portia (My University, 2017)
BACKGROUND In sports rehabilitation, physiotherapists use physical screening tests at the beginning of the season to ascertain the current musculoskeletal condition of athletes. Early identification of risk of injury through pre-participatory screening is used to minimise injury. The pre-participatory screening tool used should be accurate and practical and must contain tests that are reliable. The objectives of this study were to establish the intra-rater and inter-rater reliability of the one-legged hyperextension test, empty can and full can shoulder impingement test, standing stork test, bridging hold test and the 747 balance test. METHODS A reliability study was conducted where data were collected from the University of the Witwatersrand’s Cricket and Football Clubs during August 2015. Ethical approval was given by the Human Research Ethics Committee (HREC) of the University of Witwatersrand (Protocol number: M150626). The screening tests were conducted by two qualified physiotherapists, each with at least five years of clinical experience. Thirty five healthy, uninjured, male cricket and football players participated in the study. Players who had undergone surgery to the spine or limbs in the past were excluded. The following tests were included: the one-legged hyperextension test, bridging hold test, the 747 balance test, the empty can and full can shoulder impingement test and the standing stork test. The study took place over a period of two weeks where day 1 was for assessment 1 and day 2 was for assessment 2. These assessments occurred around the same time of day so that the athlete was exposed to the same conditions for both assessments. This was either before practice session, during practice sessions or after practice sessions. Data were analysed to establish intra- and inter-rater reliability. Cohen’s kappa was used for the one-legged hyperextension test, empty can and full can impingement test and the standing stork test. The Intraclass correlation coefficient (ICC) was used for the bridging hold test and the 747 balance test. A confidence level of 95% (p≤0.05) was applied as the criterion for determining statistical significance. RESULTS The intra-rater reliability was found to be moderate to substantial in the empty can test (k=0.6-0.8;95%CI:0.4–1.2; p<0.001); no agreement to moderate in the full can test (k=0.1–0.6;95%CI:-0.1–1.1;p<0.001); fair to moderate in the one-legged hyperextension test (k=0.4–0.6;95%CI:0.1–0.9;p<0.001); no agreement in the standing stork test (k=-0.06–0.1;95%CI:-0.4–0.7;p<0.05); fair to moderate in the bridging hold test (ICC=0.3– 0.5;95%CI:-0.4–0.7;p<0.05); and fair to moderate in the 747 balance test (ICC=0.2–0.6;95%CI:-0.4–0.8; p0.05). The inter-rater reliability was found to be substantial to excellent in the one-legged hyperextension test (k=0.8-0.9; 95%CI:0.7–1.1;p<0.001), bridging hold test (ICC=0.8–0.9; 95%CI:0.6–0.9; p=0.008) and substantial in the full can test (k=0.8;95%CI:0.5–1.1;p<0.001); no agreement to substantial in the empty can test (k=-0.05–0.8;95%CI:-0.1-1.1;p>0.05); no agreement in the standing stork test (k=-0.06–0.3;95%CI:-0.2–1.3;p>0.05) and fair to substantial in the 747 balance test (ICC=0.2–0.7;95%CI:-0.2–0.9;p< and >0.05). CONCLUSION This study shows there is moderate to substantial intra-rater reliability for the empty can test. This study also shows there is substantial to excellent inter-rater reliability for the one-legged hyperextension test, the bridging hold test, and substantial inter-rater reliability for the full can test. The reliability of these tests is acceptable and can therefore be used with confidence as part of the screening tools, on condition that validity is intact. Further in-depth studies still have to be done for the 747balance test as this test consists of a number of components which need to be assessed individually. It is also suggested that the standing stork test be removed as a field–based screening test as this test demonstrated no agreement within a rater and no agreement among the raters.
A research report submitted to the Faculty of Health Sciences, University of the Witwatersrand, Johannesburg in partial fulfilment of the requirements for the degree of Master of Science in Physiotherapy Johannesburg 2017.
Keywords: Pre-Participatory Screening; Sports